Consumer Protection for Health Services for Poor Patients (Case Study of Mengwi Public Health Center 1) - Rai Widiatmika; A. A. A. Ngr. Sri Rahayu Gorda (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Health is the right of all citizens as mandated in the 1945 Constitution, so health services should not discriminate against patients based on certain groups. In fact, in Indonesia there is still a phenomenon where patients are compartmentalized based on their economic and social groups. This has led to several cases of patient rejection and delayed treatment due to administrative constraints. In the light of this phenomenon, this study seeks to examine the form of legal protection that indigent patients must obtain in health services, especially for BPJS or KIS patients. The Mengwi I Health Center as a community health service center should provide maximum service, but there are still some obstacles in service related to underprivileged patients due to administration. This research is a type of empirical legal research with a statutory regulation approach, data collection is done by interviews. The results of this study indicate that the implementation of health rights services for underprivileged patients at Wangaya I Health Center has been carried out based on Law Number 36 of 2009 and Law Number 44 of 2009, Law Number 8 of 1999 concerning Consumer Protection, Law Number 36 of 2009 concerning Health and Law Number 44 of 2009 concerning Hospitals. Legal remedies that are usually taken by incapacitated patients if they do not receive health services from the hospital are to question the management of the Wangaya I Health Center and report this to members of the local DPRD. In addition, patients can also file a civil lawsuit in accordance with the Civil Code.